A Case of Left Haemothorax from Contained Rupture of Penetrating Atherosclerotic Ulcer - Chan, Yen Ming; Matossian, James; Renwick, Bryce (International Journal For Research In Health Sciences And Nursing, 2018)
Penetrating Atherosclerotic Ulcer (PAU) is a rare clinical entity of Acute Aortic Syndrome (AAS). The rupture rate for PAU is almost ten-times that of aortic dissection but the clinical diagnosis of this condition can be challenging due to numerous other condition presenting with similar symptoms of “aortic pain”. However, with a unique prognosis, treatment strategy is distinct and prompt diagnosis with early specialist input is needed. We report a case of PAU presenting with collapse, chest and abdominal pain with a left Haemothorax.